Use of the eGlycemic Management System by Glytec Provides Safe and Effective Glucose Control for Cardiac Surgery Patients Managed on Intravenous Insulin Therapy - Aloi, J.; Chidester, P.; Henderson, A.B.; McFarland, R.S.; Booth, R.; Mabrey, M. (My University, 2015)
Attached